A PERSPECTIVE ON GLOBAL FOOD SECURITY-WHERE FROM HERE? - Acram Taji; Tanya Tapingkae (Central Laboratory for Genetic Resource and Molecular Biology, Faculty of Agriculture, Udayana University in cooperation with Asia-Oceania Bioscience and Biotechnology Consortium (AOBBC), 2012)
A PERSPECTIVE ON GLOBAL FOOD SECURITY-WHERE FROM HERE?